Integration of genomic databases and bioinformatic approach to identify genomic variants for sjogren’s syndrome on multiple continents - Anisa Nova Puspitaningrum; Dyah Aryani Perwitasari; Wirawan Adikusuma; Gina Noor Djalilah; Haafizah Dania; Rita Maliza; Imaniar Noor Faridah; Made Ary Sarasmita; Melodia Rezadhini; Rocky Cheung; Lalu Muhammad Irham (Media Farmasi: Jurnal Ilmu Farmasi, 2022)
An autoimmune disorder is an abnormality that causes a disease. It is caused by a weakened immune system. One of the autoimmune diseases is Sjogren’s syndrome, which affects the salivary and lacrimal glands and causes dry mouth, dry eyes, and dry skin. Sjogren’s syndrome influences humans of every age, with the symptoms occurring at the age of 45–55 years and rarely in children. One of the factors causing Sjogren’s syndrome is genetic disorders. To identify genes that can influence Sjogren’s syndrome in this study, we used several databases, including GWAS Catalog, HaploReg Version 4.1, GTEX portal, and Ensembl, particularly to identify the gene expression profiles of TNIP1, TNFAIP3, and IRF5 and the quantitative properties of locus’ expression. This research showed that the missense variants and splice donor rs2233290, rs2230926, and rs2004640 influenced the susceptibility of autoimmune diseases, especially Sjogren’s syndrome, in the fibroblast tissue, sigmoid tissue, sigmoid colon, skin, esophagus, and adrenal glands. The allele frequency of each variant was then assessed in African, American, European, and Asian populations. Our data showed that TNIP1, TNFAIP3, and IRF5 genes in African and American populations had higher frequencies than in the Asian population. This implies that the last of the aforementioned populations might be relatively susceptible to the autoimmune disease Sjogren’s syndrome.